FORMULATION OF MESALAMINE-LOADED RECTAL MUCOADHESIVE PELLETS FOR THE TREATMENT OF INFLAMMATORY BOWEL DISEASE USING 32FULL FACTORIAL DESIGN - VAJA, PAYAL N.; DETROJA, CHETAN M. (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of the present work was to optimize a rectal suppository containing mucoadhesive pellets of Mesalamine to achieve local yet sustained release of Mesalamine for once-a-day administration for the therapy of Inflammatory Bowel Disease. Methods: Thus, the present work involves forming mucoadhesive pellets of mesalamine by extrusion spheronization, which were then loaded into a suppository to be administered rectally. The pellets were evaluated for mucoadhesion strength, swelling potential, morphology, particle size, drug release, drug loading and retention time. Results: The optimized batch of pellets using Eudragit RLPO as the release retardant, carrageenan as a mucoadhesive polymer and other excipients had a mucoadhesion strength of 0.143 N, a swelling index of 50.50 %, and 44 % and 75 % drug was released from them at the end of 6 and 15 h respectively. The pellets-loaded cocoa butter suppositories had a melting range of 35–37 °C, disintegrated within 8–9 min and had a hardness of 4–5 kg/cm3. A comparison of the in vitro drug release profile from the mucoadhesive pellets and the mucoadhesive pellets-loaded suppositories showed a closeness in the % cumulative drug release indicating that cocoa butter did not interfere in the release of the drug from the pellets. Conclusion: Mucoadhesive Pellets were successfully developed by extrusion spheronizer technique and incorporated into suppositories. In vitro study revealed a release profile that warranted a once-a-day regimen leading to a reduction in the requirement of the drug and hence the side effects.